The painter's discipline: aesthetics and form in Scottish painting. Issue 5 (20th October 2022) - Hodson, E. A.
Abstract : This paper concerns the practice of Glasgow-based painter Louise Hopkins. Most known for her detailed, laboured repainting of furnishing fabrics, Hopkins appropriates found images and everyday mass-produced fabrics into her work. Founded on the interstices between semiotics and formalism, her aim is the turning of found images into painting. Unravelling this particular aspect of her practice will form the central concern of this paper. Based on ethnographic research with the artist, this paper will explore the artist's commitment to the discipline of painting through the lens of an anthropological analysis and specifically, how her work evokes modernist concerns with aesthetics and formalism long since thought dead. In what follows I will address how artists are currently engaged with aesthetic concerns, ensuring its continual transformation and revival and how, like the medium of painting itself, its prophesied death has never really materialised.